The three musketeers - Cameron, Joan; Dumas, Alexandre Hayden, Sean Valenza, Valeria (Ladybird London, 2013)
"D'Artagnan travels to Paris to become a Musketeer and quickly finds himself caught up in high adventure and intrigue at the royal court. With his new-found friends, Athos, Porthos and Aramis, D'Artagnan risks his life in the service of the queen"--Page 4 of cover